1999
DOI: 10.1016/s0014-5793(99)01279-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tau phosphorylating protein kinase cdk5 prevents β‐amyloid‐induced neuronal death

Abstract: The key target of this study was the tau protein kinase II system (TPK II) involving the catalytic subunit cdk5 and the regulatory component p35. TPK II is one of the tau phosphorylating systems in neuronal cells, thus regulating its functions in the cytoskeletal dynamics and the extension of neuronal processes. This research led to demonstration that the treatment of rat hippocampal cells in culture with fibrillary L L-amyloid (AL L) results in a significant increase of the cdk5 enzymatic activity. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
155
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(168 citation statements)
references
References 42 publications
12
155
0
1
Order By: Relevance
“…A␤ neurotoxicity has been reported to result in tau hyperphosphorylation (11)(12)(13)(14)(15)(16)(17)(18). In agreement with these findings, we have previously shown that the addition of fibrillar A␤ to mature hippocampal neurons kept in culture for more than 28 days resulted in the sustained activation of MAPK (14,18).…”
Section: Fibrillar A␤ Activated Mapk In Hippocampal Neurons Obtained supporting
confidence: 79%
See 1 more Smart Citation
“…A␤ neurotoxicity has been reported to result in tau hyperphosphorylation (11)(12)(13)(14)(15)(16)(17)(18). In agreement with these findings, we have previously shown that the addition of fibrillar A␤ to mature hippocampal neurons kept in culture for more than 28 days resulted in the sustained activation of MAPK (14,18).…”
Section: Fibrillar A␤ Activated Mapk In Hippocampal Neurons Obtained supporting
confidence: 79%
“…In addition, several groups have reported that kinases known to phosphorylate tau in vitro were activated in response to fibrillar A␤ deposition. When young neurons were incubated in the presence of fibrillar A␤, both GSK3␤ and CDK5 were activated (11,17). In mature hippocampal neurons, on the other hand, fibrillar A␤-induced neurotoxicity was accompanied by the sustained activation of mitogen-activated protein kinase (MAPK) (14)(15)(16)18).…”
mentioning
confidence: 99%
“…Nevertheless, overexpression of p25 in cultured neurons leads to cytoskeletal disruption, hyperphosphorylated Tau, and apoptotic cell death (16). Cdk5 activity is deregulated in hippocampal neurons by A␤ fibrils, resulting in the activation of Cdk5 and hyperphosphorylation of Tau (68,69). Probably because of its multifunctional role in the nervous system, aberrant Cdk5-p25 activity looms as a major factor in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 32 Many of the pathologic epitopes on hyperphosphorylated tau in the brains of Alzheimer's disease patients were thought to be generated by sequential phosphorylation by different tau kinases. For example, phosphorylation of a specific amino acid residue by CDK5 is a prerequisite for the subsequent kinase action of glycogen synthase kinase-3␤ (22,23 The association of CDK5 with a particular activator unit, p35 or p25, provides a novel mechanism of controlling kinase characteristics.…”
Section: Discussionmentioning
confidence: 99%